Fast recognition of natural feature identifiers by a mobile phone - Katona, Melinda; Nyúl, László G. (Acta Cybernetica, 2015)
One of the most important and widely used technique for automatic identification is the use of visual codes. Identifiers encoded in various symbols and patterns make electronic reading possible, that greatly helps and speeds up processing, e.g., at cashier lines, warehouse transactions, high speed processing places, production lines. The common codes designed using geometric patterns usually identify types or entities. However, patterns can be produced that, by their nature, are unique and thus can be used to validate originality or authenticity. In this paper, we focus on the automatic localization and recognition of a kind of natural feature identifier (NFI). We present an image processing algorithm that successfully locates NFI code region in an image taken by a mobile camera and extracts features of the NFI glitters that can be the basis for recognition. We also show preliminary experimental results.